Comparative study on two different methods for fabrication of sustained release boscalid based on mesoporous silica - Wenjing Li; Xuewan Xu; Hua Pan; Litao Wu; Shiyang Bai; Jihong Sun; Fang Zhang (Materials Research Express, 2021)
In this study, boscalid silica nanosphere nanoparticles (Bos@SNS/t Nps) and boscalid bimodal mesoporous silicas material nanoparticles (Bos@BMMs Nps) were prepared using two different methods. A comparative study on characteristics and properties of two nanospheres were conducted. Both nanoparticles had spherical shapes with average diameters of 719.3 ± 6.3 nm (Bos@BMMs) Nps and 981.3 ± 4.8 nm (Bos@SNS/t) Nps. The structures of nanoparticles were characterized by scanning electron microscopy, X-ray diffraction, dynamic light scattering laser particle-size analysis, and fourier transform infrared spectroscopy, indicating that Nps had a well-defined core–shell construction for efficient loading of Bos. The loading rates of Bos@BMMs and Bos@SNS/t Nps were 25.2 ± 2.3% and 27.3 ± 3.6%, respectively. The nanoparticles had obvious pH sensitivity, and the release of Bos in pH 9.0 was higher than those in pH 7.0 and pH 4.0. No significant difference in the release behavior of nanocomposites was found, and the release models were fitted with the Weibull equation. Finally, the bioactivity of the Bos-loaded nanocomposite was measured against Rhizoctonia solani , which showed that the fungicidal efficacy of Bos@SNS/t was slightly better than that of Bos@BMMs.